MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP MENGGUNAKAN E-MODUL BERBASIS PROBLEM BASED LEARNING - Tri Lestari Budi Asih; Baskoro Adi Prayitno; Sri Retno Dwi Ariani (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the effectiveness of problem-based learning-based e-modules on pressure materials and their application in daily life to improve students' problem-solving skills. This research is a type of R&D research that uses the design of a Non-equivalent Pretest-Posttest Control Group with a sampling technique, namely purposive random sampling. The instruments used to obtain data include a reading interest test adapted from Khoiriah et al. (2020) and a problem-solving skills essay test based on pressure material indicators whose results are analyzed by the N-Gain Score test. The subjects of this study were two science teachers and 64 students of class VIII of SMPN 2 Colomadu. They were divided into 32 students in the experimental class and 32 in the control class. The research results showed that problem-based learning-based e-modules on pressure materials and their daily application improved students' problem-solving abilities of SMP N 2 Colomadu